2015
DOI: 10.1007/s00442-015-3317-3
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns of energy equivalence in temperate soil invertebrates

Abstract: The question whether total population energy use is invariant to species body size (the energy equivalence hypothesis) is central to metabolic ecology and continues to be controversial. While recent comparative field work and meta-analyses pointed to systematic deviations of the underlying allometric scaling laws from predictions of metabolic theory none of these studies included the variability of metabolic scaling in ecological time. Here we used extensive data on the invertebrate soil fauna of Kampinos Nati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 77 publications
4
10
0
Order By: Relevance
“…protists that had relatively low density (but see discussion below) and flattened overall abundance -body mass scaling. Correspondingly, macroconsumers had higher biomass and used more energy than is expected by biomass and equivalence rules in our and other published large-scale empirical studies (Ehnes et al 2014, Ulrich et al 2015. The larger energy use by macroconsumers supports allometric degree Accepted Article hypotheses, as they are able to feed on a wider range of food items and thus having access to more energy (Ehnes et al 2014).…”
Section: Accepted Articlesupporting
confidence: 80%
See 4 more Smart Citations
“…protists that had relatively low density (but see discussion below) and flattened overall abundance -body mass scaling. Correspondingly, macroconsumers had higher biomass and used more energy than is expected by biomass and equivalence rules in our and other published large-scale empirical studies (Ehnes et al 2014, Ulrich et al 2015. The larger energy use by macroconsumers supports allometric degree Accepted Article hypotheses, as they are able to feed on a wider range of food items and thus having access to more energy (Ehnes et al 2014).…”
Section: Accepted Articlesupporting
confidence: 80%
“…Across all size classes we observed average abundance -body mass scaling of -0.54, which is flatter than the expected scaling of -0.75. Similar large-scale studies across temperate forests in Germany and Poland showed slopes of -0.68 across trophic groups (Ehnes et al 2014) and -0.58 in decomposers (Ulrich et al 2015). Our data are at the lower end of published estimates potentially due to inclusion of wider range of size classes, i.e.…”
Section: Accepted Articlesupporting
confidence: 70%
See 3 more Smart Citations